A response to Brennan: Epistocracy undermines democratic society - Julian, Abby Gayle N. (Animo Repository, 2024)
Jason Brennan favored the notion of epistocracy in democratic states as a decision-making strategy for distributing political power to vote in The Ethics of Voting. In Against Democracy, Brennan further elaborated on the epistocracy and why there is a need for such. His reasons are based on irrationality, political ignorance, and bias of people in politics. Epistocracy implies that those knowledgeable possess the power to rule. Those with sufficient reasons for voting should vote and those who vote badly should abstain. He believed that this could bring people a better government which they benefit from. I utilized the ideal rule utilitarianism framework to challenge the Epistocracy of Brennan. It is a theory under the moral consequentialist adheres to follow a rule that results in the greatest good. I made epistocracy an ideal rule in a democratic society and analyzed its outcomes in society. This paper argued that Brennan’s epistocracy is wrong and through the lens of ideal rule utilitarianism, this paper showed that epistocracy led to social disharmony. The question that this paper provided an answer to is, "Does epistocracy entail the greatest good of a democratic society?” I claimed that epistocracy undermines democratic society as it leads to social disharmony in the form of elitism and bias. The paper also provided an ideal rule utilitarian analysis on elitism and the aggravation of confirmation, disconfirmation, and motivated bias due to the unequal distribution of voting power and the information gap.